A correlational study on personality maturity and self-esteem - Abrajano, Mary Jean G. (Mary Jean G. Abrajano, 1999)
This study involved 30 UP Tacloban College students, who were deliberately selected from three randomly chosen course classes. This research was conducted to determine the degree of relationship between Personality Maturity (PM) and Self-esteem (SE). Two tests were administered : personality maturity test and self-esteem test. The researcher used the Person's Product Moment correlation Coefficient formula to obtain the degree of their relationship. It was found out that there is a high positive between the two, however this relationship is non causal because this study is only correlational.